Cardiovascular Disease and Type 2 Diabetes Risk Across Occupational Groups and Industry in a Statewide Study of an Australian Working Population. Issue 3 (March 2018) - Kelsall, Helen Louise; Fernando, Palamandadige Harsha Suranga; Gwini, Stella May; Sim, Malcolm Ross
Abstract : Objective: The aim of this study was to investigate prevalence of type 2 diabetes (diabetes) and cardiovascular disease (CVD) risk in occupational and industry groups in a large, diverse working population. Methods: Five hundred thousand Victorian workers undertook health checks, including lifestyle, anthropometric, and biomedical cardiovascular risk factor assessment. Five-year diabetes (AUSDRISK) and absolute CVD risk were estimated. Results: High diabetes and CVD risk was increased in many occupational groups and industries relative to managers and Professional/Scientific/Technical Services, respectively. Significantly more blue-collar workers had high diabetes risk [males prevalence ratio (PR) 1.19 (95% confidence interval, 95% CI 1.17 to 1.20); females 1.34 (95% CI 1.30 to 1.38)], high CVD risk [males 1.45 (95% CI 1.37 to 1.53); females 1.48 (95% CI 1.17 to 1.88], and risk factors including smoking [males 2.26 (95% CI 2.22 to 2.30); females 2.20 (95% CI 2.13 to 2.27)], compared with white-collar workers. Conclusion: Targeting occupational and industry groups within sustainable workplace programs could assist in reducing chronic diseases, lowering sickness absence, and improving productivity. Abstract : Supplemental Digital Content is available in the text